Designing At-Work-Conversation Based Materials for Diploma III Midwifery Program - Haryani, Surip (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
The study is aimed to find out the midwifery students’ need for the materials that they can use to learn English that is appropriate with their field as midwifery students, to describe the design of At-Work Conversation based materials for midwifery Students, and to find out the effectiveness of the materials to increase the students’ ability in making conversation in working situation or in improving the students’ communication skill. This is a Research and Development study (R and D). The researcher used theories of ESP material design Proposed by Hutchinson and Waters and John Munby in conducting the research. The procedure of the research consists of 3 steps namely exploring, designing product, and implementation and evaluation stages. In step one, the researcher conducted need analysis and investigating the existing product for the English teaching in Midwifery program of STIKES Muhammadiyah Gombong. In step 2, the researcher designed syllabus and the first draft of the materials based on the need analysis. In step 3, the researcher tried out the materials, and asked evaluation for the first draft of the materials and revised the first draft based on the evaluation results and wrote the final draft of the materials. Before the application of the materials, the researcher conducted the pre and post test to find out the effectiveness of the designed materials to improve the students’ communication skill. Based on the need analysis the researcher found that the midwifery theme based English materials were needed in line with the competence based curriculum applied in the Midwifery Program. The researcher designed the materials based on the communicative competences for midwifery students in 9 (nine) units namely I am a Midwife, Admission in a Private Midwife Clinic, Checking Vital Signs, Antenatal Care (ANC), Assisting Labor/ Childbearing, Dealing with Post partum women, Newborn Care, Family Planning and reproductive health Counseling and Providing Child health care. Each unit consists of four basic elements (sub titles). The effectiveness on the product can be shown from the improvement scores on the post test. The dependent sample T-Test statistic result shows value Sig (2-Tailed) 0.000 or less than 0.05 which means that score improvements of the pre and post test are significant. The results of the optional questioners given to the experts and students indicate positive mean and mode scores which mean that they mostly agreed with the statements on the questioners and agreed with the designed materials. It can be concluded that the materials made by the researcher are suitable for the midwifery students. Keywords: Designing English Material, Midwifery English, R and D